Safety and Efficacy of the Combination of Amitriptyline and Pregabalin SR in Severe Neuropathic Pain: Data of Logic Trial - Kiran, Dr. Mayuresh Dilip; Pawaskar, Lalit; Sheikh, Shaheen Naseem (International Journal of Innovative Research in Medical Science, 2019)
Objective: To evaluate the safety and efficacy of the combination of Amitriptyline and Pregabalin SR in patients of severe neuropathic pain not controlled on monotherapy of a neuroanalgesic. Methods: LOGIC Study was conducted at 120 centres on 1269 patients across India. Patients above 18 years with severe neuropathic pain not controlled on monotherapy of a neuroanalgesic and who satisfied the inclusion and exclusion criteria were enrolled in the study. A combination of Amitriptyline and Pregabalin SR was given once daily. Patients were evaluated for the efficacy by visual analogue scale (VAS) and score was noted at 3 visits. Safety was evaluated through noting the adverse events occurring during the study. Change in mean VAS score, percentage of patients achieving ≥ 50 % reduction in pain at every visit and Number Needed to Treat (NNT) was assessed. Results: Mean VAS score was 7.87 at baseline, 5.6 at day 7 and 3.42 at day 21. 46.4 % and 84.6 % of total patients at day 7 and 21 respectively had a reduction in pain of ≥ 50 % from the baseline. NNT was calculated to be 1.19 for achieving ≥ 50 % pain relief. Reduction in pain intensity was irrespective of blood glucose control, age and gender of the patient. Adverse effects were observed in 15 % patients of patients - Sedation, Dizziness, Dry Mouth and Constipation were predominant. Conclusion: Combination of Amitriptyline and Pregabalin SR is safe and efficacious in the treatment of severe neuropathic pain.